Tax For Australians For Dummies - Prince, Jimmy B. (Wiley, 2014)
Lodge your tax return and maximise your refund Keep on top of changes to the rules Minimise your small business tax bill Make the most of tax-free investing and super Get the most from your next tax return with this essential guide Whether you're an employee, investor, small business owner, retiree or even a student, Tax for Australians For Dummies has all the information you need to get every cent you're entitled to for the 2013-14 tax year. This book guides you step-by-step through the complex Australian tax system to help you understand exactly what you can claim and what you're owed! Understand what you can and can't claim - lodge your tax return correctly or deal with an audit Decipher small business tax - keep on top of record keeping and claim the right expenses and concessions Find out about tax-effective investing - take advantage of investing in shares and property Get ready for the future - explore tax rules for superannuation and the benefits of using a self-managed super fund Open the book and find: Tips for reducing your tax bill and maximising your refund Case studies with practical step-by-step examples Advice on income tax and GST Information for families with children How to calculate capital gains tax and fringe benefits tax Ways to spot and avoid common tax mistakes